Potential for Development of Mosque-Based Halal Tourism in Lombok, West Nusa Tenggara Province - Rachman, Abdul; Muizzudin; Haura, Arie; Aisyah Defy R. Simatupang (Universitas Muhammadiyah Yogyakarta, 2024)
This research analyzed and explored the potential for developing mosque-based halal tourism on the island of Lombok, which is known as the Island of a Thousand Mosques and is rich in culture and nature. Several mosques in Lombok have historical value, architectural beauty, and regional culture, which can be used as a unique tourist activity experience for Muslim and foreign tourists visiting mosques in Lombok, West Nusa Tenggara Province. This research used a descriptive qualitative method to describe the potential for developing mosque-based halal tourism in Lombok. Primary data sources were obtained through interviews and observations at the Hubbul Wathan Mosque or the Mataram Islamic Center Mosque, a mosque that is used as a halal tourist destination. This research shows that the potential for developing mosque-based halal tourism is very large and has an innovative concept because it can increase the number of tourists and increase the variety of halal tourist destinations in Lombok. This research also explored important aspects of developing halal tourism, including accommodation facilities, halal food, and activities based on Islamic culture. Mosque-based halal tourism centers can offer a holistic experience for Muslim tourists, including visiting historic mosques, learning about local Islamic culture, and enjoying regional halal culinary specialties. The potential for developing mosque-based halal tourism in Lombok, West Nusa Tenggara Province, is an attractive opportunity to attract more Muslim tourists and foreign tourists to visit mosques in Lombok.